Characteristics of the population with mild COVID-19 symptoms eligible for early treatment attended in a single center in Northern Italy. Issue 1 (January 2023) - Magro, Paola; Degli Antoni, M.; Formenti, B.; Viola, F.; Castelli, F.; Amadasi, S.; Quiros-Roldan, E.
Abstract: After more than two years from the first COVID-19 detected case in Brescia, Northern Italy, monoclonal antibodies and antiviral therapy aimed at early treatment of mild COVID-19 in patients at risk of progression and of hospitalization has been approved in Italy. Here we report the characteristics of the population eligible for the COVID-19 early treatments at our COVID-19 Early Therapy Unit of the Infectious Diseases Department of the ASST Spedali Civili of Brescia, with the aim to evaluate the characteristics of the foreign and native groups. Up to March the 31st, 2022, a total of 559 patients were referred to our Unit for COVID-19 early treatment, where 7.6% were foreigners, a group significantly younger than natives (p < 0.05). Particular differences are noticed between the native and the foreign population, where people aged > 65 years old were significantly more frequent among italians (39.7% vs 16.3%, p < 0.01), while primary or acquired immunodeficiencies were more frequent in foreigners (55.8% vs 38.9%, p = 0.03). Substantial differences are noted between native and foreign populations, where 14% and 26% (p < 0.05) respectively have never been vaccinated for COVID-19. Overall, 71% of the referred patients received an early treatment for mild COVID-19, with no differences between the two groups. Overall, on day 28 after treatment, 23 (4%) patients had been hospitalized due to COVID-19 related complications and four died (0, 7%), no one was foreigner. In conclusion, while the treatment offered for mild COVID-19 appears to be rather uniform between the native and the foreign populations, some differences, especially in preventive vaccination COVID-19, must be taken into account.